LEV TOLSTOYNING “Urush va tinchlik” ROMANIDAGI PERSONELLARNING ICHKI DUNYOGA URUSHNING TA’SIRI.: AYNUR BADALOVA ZAHIR (Scientific journal of the Fergana State University, 2024)
War is one of the main themes of world literature. And this is not surprising - because true essence of each person is revealed in the war. If we look at all the works written about war in the world literature, we can come to the general conclusion of the literature about war: War is a destructive force, a tragedy of people's lives. War can destroy the culture, state, language, and people built up over hundreds of years in a few days. Literature is an expression of humanistic thought, and for this reason, in its works, it calls all humanistic people of the earth to condemn war.In the article, the theme of war and the impact of the truths of war to the inner world of a person are expressed in Leo Tolstoy's novel "War and Peace". Here, the spiritual sufferings of Tolstoy's characters, the horrors of war are reflected through feelings, which showed the writer's deep understanding of the essence about the inner world of man and expressed it through various means.